Aquaponics System Implementation in Catfish Farming at Labruk Lor Village, Lumajang District, Lumajang Regency - Hertika, Asus Maizar Suryanto; Nurlaelih, Euis Elih; Shofwan, Shofwan; Putra, Renanda Baghaz Dzulhamdani Surya; Alfarisi, Muhammad Asnin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2024)
Decreasing water quality and disease outbreaks are negatively affecting catfish farming in Labruk Lor village, Lumajang district, leading to reduced productivity and income for catfish farmers. Service Doctoral Grant programme aims to address issues by offering counselling, training, and optimising yard use through aquaponic activities within the Rumah pangan lestari (RPL) programme. This project is a collaboration between BUMDES Labruk Lor Village, the fish cultivator group